Presentation Feature of Lymphoma in the Kirkuk City - Abdulkarim, Suhair Sheriff; Sheriff, May Mohammad; Jasim, Mustafa Zuhair; Ali, Mohammad Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Lymphoma is one of the commonest cancer in the Iraq. While the incidence is only 3 % in the western world, in the middle ease almost 10 % of all cancer are lymphoid. Because of the advanced medicine in the developed world, most of the cases are diagnosed at early stages of the disease. In the underdeveloped and even developing world the situation seems to be different. The true object of this study was to screen our lymphoma patients at presentation to see the stage and pattern of their disease. This is simple descriptive study; performed from July 2018 to June 2019 that reviewed retrospectively in Kirkuk hematology oncology Cancer in Kirkuk city. The total number collected were 126 patients, the information were taken from records of the file system assigned for each patient in Kirkuk hematology oncology Cancer, Cases newly diagnosed with lymphoma, both sexes over ten years old were eligible to participate in this study. Stages of lymphoma are based on time of presentation and staged according to the Ann Arbor system, takes both types Hodgkin and Non Hodgkin Lymphoma with their subtypes and presence or absence of B symptoms. Lymphoma simply means cancer of lymph nodes and the lymphatic tissues in the body and most commonly occurring hematological malignancies which are comparable with other countries and consider as highly curable cancer in our patients. The frequency of Non Hodgkin lymphoma which is higher than Hodgkin lymphoma. Nodular sclerosis was the commonest histopathologicl subtypes in Hodgkin lymphoma, while in Non Hodgkin lymphoma diffuse large B cell was common. In Hodgkin lymphoma we found that peak age group of presentation was younger than Non Hodgkin lymphoma, male predominance in NHL & female predominance in HL and absence of B symptom are more common in our study.